'It's on my head': Risk and accountability in public order policing. (March 2023) - Leach, Ian
Heavy policing remains 'a chronic feature of public order operations' (Waddington PAJ (1994) Liberty and Order: Public Order Policing in a Capital City. London: UCL Press), both in the form of officer numbers and in the proportionality of tactics employed. This paper argues that at the heart of this lies the assessment of threat and risk and how police commanders perceive, predict and manage the potential for disorder. It reports on the findings of a mixed-methods study, combining data from observations of three separate public order events, with in-depth interviews of seven high-level, police public order commanders from five different UK police forces. Analysis suggests that commanders construe 'risk' in very broad terms, seeking to mitigate not only physical harm but also abstract consequences such as reputational damage and loss of public confidence. Structured models central to the task of threat and risk assessment give the appearance of a quantitative and objective process. However, the actual appraisal of threat and risk, both before and during public order operations, is almost entirely heuristic. Furthermore, the analysis suggests commanders' decision-making is acutely affected by the pressure of accountability. It is argued that at a tacit level, their threat and risk assessments reflect this and a direct consequence is the deployment of additional police resources. At a time when the police service is under intense pressure to do more with less, this paper discusses how refining the assessment of threat and risk may prove to be a critical factor in the delivery of cost effective and proportionate public order policing.